MODELLING THE DYNAMICS OF THE SUBJECT OF MASS COMMUNICATION MENTALITY - Даніч, В. М. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The paper outlines the modelling concept of the dynamics of susceptibility of the subjects of mass communication to the effects of inductors. The level of susceptibility is one of the key characteristics of the subject’s mentality, as a system of feelings (likes and dislikes), stereotypes, values, ideas about the world, which are formed in the mind during key periods of his life (childhood, becoming, social and political disasters, etc.). The changes in the structure of this system, its key characteristics – levels of perception, as well as the impact (induction) of certain views on social phenomena are determined as the dynamics of mentality. The probability of transition of the recipient from one socio-psychological state to another depends on the levels of perception and influence in a pair of recipient-inductor. Such dependence is adopted as multiplicative. Transitions from state to state under the influence of various factors may be accompanied by changes in the levels of perception and impact, which are determined by the dynamics of mentality. Mathematical models of this dynamics are offered in the form of iterative schemes, finite probabilistic automata. The states themselves can be viewed as structures (vectors, in particular), their components (impact and perception levels, types of behavior, in particular) - as linguistic variables that take on the values of vague variables, which, in turn, are determined by the characteristic functions of vague sets. It was determined that iterative schemes should be applied with variability (possible changes) of the state structure, dynamism of the set of states (some states are not known in advance, possible emergence of new states). For impact and susceptibility levels (the number of which, in case of using a vague option, is limited and known in advance, for example, zero, low, medium, high, maximum), it is recommended to use finite probabilistic automata. Fixing the transition from state to state can be carried out by sociological tools (by interviewing, questioning, etc.).